Civil rights unionism : tobacco workers and the struggle for democracy in the mid-twentieth-century South - Korstad, Robert Rodgers (The University of North Carolina Press, 2003)
Drawing on interviews with black and white tobacco workers in Winston-Salem, North Carolina, Korstad explores their confrontations against racial capitalism that consigned African Americans to the basest jobs in the industry, perpetuated low wages for all southerners and shored up white supremacy.